ROLE OF TEA DREGS LIQUID ORGANIC FERTILIZER AND PLANT MEDIA COMPOSITION IN INCREASING TOMATO RESULTS (Lycopersicon esculentum Mill.) - Maryana, Maryana; Haryanto, Darban; Lifia, Reti Columba (Universitas Pembangunan Nasional Veteran Yogayakarta, 2023)
The aim of this study was to determine the composition of the tea waste liquid organic fertilizer and the composition of the growing media in increasing the yield of tomato plants. The research was conducted from June to November 2022 at the Wedomartani Experimental Garden, Faculty of Agriculture UPN